Factors Relating to Patient Compliance with Hypertension Management in the Era of the Covid-19 Pandemic - Sari, Lulu Permata; Septiwi, Cahyu; Santoso, Dadi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Hypertension is abnormally high blood pressure and a serious health problem in the world that causes morbidity and mortality. Uncontrolled hypertension can cause serious complications such as coronary heart disease, stroke, kidney disease, vision problems and is one of the comorbid diseases during the Covid-19 pandemic. Compliance to hypertension manajement to control their blood pressure is very importantto avoid hypertension’s complications and death. This study aim to determine the factors related to patient compliance with hypertension management in the era of the Covid-19 pandemic. This research method uses a descriptive analytic method with a cross sectional approach. The sample consists of 100 respondents, data collection using a questionnaire and analyzed using univariate and bivariate analysis. There is a relationship between age and patient compliance with hypertension management (p=0.016). There is a relationship between knowledge and patient compliance with hypertension management (p=0.020). There is a relationship between motivation and patient compliance with hypertension management (p=0.045). There is a relationship between family support and patient compliance with hypertension management (p=0.018). There is a significant relationship between factors of age, knowledge, motivation, and family support with patient compliance with hypertension management. Factors related to patient compliance in managing their disease are very important and need to be considered and improved in an effort to maintain blood pressure stability in hypertensive patients to avoid complications and death.